The neuregulin receptor ErbB-4 interacts with PDZ-containing proteins at neuronal synapses - Garcia, Rolando A. G. (The National Academy of Sciences, 2000)
Neuregulins regulate the expression of ligand- and voltage-gated channels in neurons and skeletal muscle by the activation of their cognate tyrosine kinase receptors, ErbB 1–4. The subcellular distribution and mechanisms that regulate the localization of ErbB receptors are unknown. We have found that ErbB receptors are present in brain subcellular fractions enriched for postsynaptic densities (PSD). The ErbB-4 receptor is unique among the ErbB proteins because its C-terminal tail (T-V-V) conforms to a sequence that binds to a protein motif known as the PDZ domain. Using the yeast two-hybrid system, we found that the C-terminal region of ErbB-4 interacts with the three related membrane-associated guanylate kinases (MAGUKs) PSD-95/SAP90, PSD-93/chapsyn-110, and SAP 102, which harbor three PDZ domains, as well as with β(2)-syntrophin, which has a single PDZ domain. As with N-methyl-d-aspartate (NMDA) receptors, ErbB4 interacts with the first two PDZ domains of PSD-95. Using coimmunoprecipitation assays, we confirmed the direct interactions between ErbB-4 and PSD-95 in transfected heterologous cells, as well as in vivo, where both proteins are coimmunoprecipitated from brain lysates. Moreover, evidence for colocalization of these proteins was also observed by immunofluorescence in cultured hippocampal neurons. ErbB-4 colocalizes with PSD-95 and NMDA receptors at a subset of excitatory synapses apposed to synaptophysin-positive presynaptic terminals. The capacity of ErbB receptors to interact with PDZ-domain proteins at cell junctions is conserved from invertebrates to mammals. As discussed, the interactions found between receptor tyrosine kinases and MAGUKs at neuronal synapses may have important implications for activity-dependent plasticity.